(untitled) (Contemporary Journal of Social Science Review, 2025)
This study examines how smart tourism technology (STT) can enhance the sustainability of religious tourism destinations and foster visitor loyalty in Pakistan. Drawing on the Technology Acceptance Model (TAM) and related theories, we develop a conceptual framework in which key attributes of STT (informative, accessibility, interactivity, personalization, security) influence tourists’ technology adoption, perceived enjoyment, sustainable tourism behavior, and revisit intentions. A quantitative survey of 499 visitors at major religious heritage sites in Pakistan was conducted, and the proposed relationships were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that all five STT attributes significantly contribute to positive technology-supported tourist experiences, which in turn lead to higher technology adoption and perceived enjoyment. STT usage shows a direct positive effect on both sustainable tourism practices (β≈0.24, p<0.001) and revisit intention (β≈0.20, p<0.001). Moreover, technology adoption mediates the effect of STT on sustainable tourism, while perceived enjoyment mediates the impact of STT on revisit intention. A multi-group analysis of moderating factors reveals that memorable travel experiences significantly enhance the effect of enjoyment on revisit intention, whereas differences in tourist behavior and preferences do not substantially alter the relationship between adoption of sustainability and enjoyment. These findings underscore the pivotal role of smart technologies in enhancing pilgrim experiences, promoting eco-friendly behaviors, and fostering visitor loyalty within the context of religious tourism. The paper concludes with theoretical contributions to the literature on smart tourism and religious tourism, as well as practical recommendations for destination managers on leveraging technology to achieve sustainable and loyalty-driven outcomes.